T-Regulatory Cell Subsets in Children with Type 1 Diabetes Mellitus: Relation to Control of the Disease - Ghonaim, Mabrouk M.; El-Edel, Rawhia H.; Kamal Eldein, Samar M.; Abo El Fotoh, Wafaa Moustafa M.; Salman, Samar S. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2017)
Background: Type 1 diabetes mellitus is described as a chronic metabolic disorder characterized by aggressive immune β-cell destruction. There are a number of varied immune mechanisms for sustaining self-tolerance in opposition to the autoimmune disorders. A recessive tolerance is accomplished by thymic gland via a negative assortment of different clones, while a dominant tolerance is accomplished by the regulatory T cells (Treg) in the periphery. Treg (CD4+ CD25+FOXP3+) are subsets of T cells which have an essential role in maintaining tolerance. Objective: To evaluate peripheral Treg (CD4+; CD25+; FOXP3+) in children cohort with T1DM. Methods: This study included 64 children diagnosed with T1DM and 35 age- and sex-matched healthy children as controls. All children were clinically evaluated and subjected to assessment of complete blood count (CBC), glycated hemoglobin, surface and cytoplasmic detection of Treg by flow cytometry. Results: This study showed that the frequency of Treg (CD4+; CD25+; FOXP3+) was significantly lower in diabetic children than with normal controls (P<0.001). There was a significant (P <0.001) reduction in the Treg (CD4+; CD25+; FOXP3+) in T1DM children with uncontrolled (Hemoglobin A1c>7%) as compared to those with controlled (Hemoglobin A1c<7%) disease. Conclusion: Diminished Treg in T1DM proved that auto-reactivation of T-cell as a result of the breakdown of immune tolerance takes part in the elaboration of autoimmune disorders as T1DM. Treg may be used in immunotherapy, thus preventing T1DM development due to its pivotal role in immune tolerance.
Keywords: effector T cells